2022
DOI: 10.1128/msphere.00160-22
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Toxoplasma gondii-Induced Host Cell DNA Replication Is Dependent on Contact Inhibition and Host Cell Type

Abstract: Toxoplasma gondii chronically infects approximately one-third of the global population and can produce severe pathology in immunologically immature or compromised individuals. During infection, this parasite releases numerous host-targeted effector proteins that can dramatically alter the expression of a variety of host genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…To our best knowledge, available data on T. gondii -driven host cell cycle modulation currently refer to haplotype I tachyzoites (RH strain) and indicate that this clonal lineage might control host cell cycle progression to ease its intracellular asexual development ( Brunet et al, 2008 ; Molestina et al, 2008 ; Velásquez et al, 2019 ; Wong et al, 2020 ; Pierre-Louis et al, 2022 ). Since several typical and atypical clonal lineages of T. gondii occur worldwide and show variable pathogenicity ( Dardé et al, 2014 ; Miller et al, 2023 ), we aimed to compare recent RH data (haplotype I) ( Velásquez et al, 2019 ) with haplotypes II and III (Me49 and NED, respectively) by infecting the same host cell type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our best knowledge, available data on T. gondii -driven host cell cycle modulation currently refer to haplotype I tachyzoites (RH strain) and indicate that this clonal lineage might control host cell cycle progression to ease its intracellular asexual development ( Brunet et al, 2008 ; Molestina et al, 2008 ; Velásquez et al, 2019 ; Wong et al, 2020 ; Pierre-Louis et al, 2022 ). Since several typical and atypical clonal lineages of T. gondii occur worldwide and show variable pathogenicity ( Dardé et al, 2014 ; Miller et al, 2023 ), we aimed to compare recent RH data (haplotype I) ( Velásquez et al, 2019 ) with haplotypes II and III (Me49 and NED, respectively) by infecting the same host cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to parasite-mediated modulation of cell cycle progression, the current data showed that both NED and ME49 strains induced host cell cycle arrest in S-phase, but they differed in the control, thereby denying any haplotype-dependent reactions. Interestingly, S-phase arrest has been studied by other groups worldwide, suggesting that arrested cells were not able to incorporate new DNA molecules ( Pierre-Louis et al, 2022 ). Given that T. gondii arrests the host cell cycle equally in primary, immortalized, and tumor cells, we could suggest that it is a parasite strategy that has been maintained throughout haplotype evolution ( Brunet et al, 2008 ; Molestina et al, 2008 ; Kim et al, 2016 ; Velásquez et al, 2019 ; Pierre-Louis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immortalized human fibroblasts, HFF, were arrested in the S-phase after 6 h p.i. with T. gondii tachyzoites (Pierre-Louis et al, 2022). The G2 phase arrest in human dermal fibroblasts or a human trophoblast cell line was linked to the downregulation of cyclin B1 (Brunet et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…T. gondii is able to influence the progression of the cell cycle of the host cell and to promote its transition to the S phase, followed however by an arrest in the G2/M phase [ [58] , [59] , [60] ]. Recently, separate studies have also revealed the ability of the parasite protein TEEGR to be exported to the host cell nucleus to induce cyclin E [ [61] , [62] , [63] ]. In addition, GRA16, another parasite effector protein, is able to positively modulate the expression of genes involved in cell cycle progression, as well as p53, via its interaction with the HAUSP protein [ 64 ].…”
Section: Introductionmentioning
confidence: 99%